Reactivity of bis(thiophosphinoyl)methane CH2(PPh2=S)2 towards sulphur and ZnMe2 : synthesis and characterization of a bis(thiophosphinoyl)(thiolate)methanide Dianionic Ligand [(S)C(PPh2=S)2]2-. - Lee, Joyce Jia Shin. (2010)
The zinc derivative of the novel bis(thiophosphinoyl)(thiolate)methanide dianionic ligand [(S)C(PPh2=S)2]2- (3) has been synthesized and structurally characterized. Treatment of [CH2(PPh2=S)2] (1) with dimethyl zinc in refluxing toluene gave air-sensitive [{HC(PPh2=S)2}2Zn] (5) via elimination of methane. Unexpectedly, the reaction of 5 with di-methyl zinc and elemental sulphur in refluxing toluene afforded [Zn{(S)C(PPh2=S)2}]2 (6), consisting of two dianionic ligands [(S)C(PPh2=S)2]2- (3) coordinating to two zinc centres. A possible mechanism leading to the formation of 6 is the reaction of the methanide carbon in 5 with sulphur, followed by displacing a [CH2(PPh2=S)2] molecule. In addition, 6 may serve as a model in mimicking zinc-containing metalloproteins which contain zinc metal tetrahedrally bonded to four sulphur atoms.